An Escherichia coli Effector Protein EspF May Induce Host DNA Damage via Interaction With SMC1 - Fu, Muqing; Liang, Song; Wu, Jiali; Hua, Ying; Chen, Hanzong; Zhang, Zhikai; Liu, Jinyue; Li, Xiaoxia; Zhang, Bao; Zhao, Wei; Wan, Chengsong (Frontiers in Microbiology, 2021)
Enterohemorrhagic Escherichia coli (EHEC) O157: H7 is an important foodborne pathogen that causes human diarrhea, hemorrhagic colitis, and hemolytic uremic syndrome. EspF is one of the most important effector proteins injected by the Type III Secretion System. It can target mitochondria and nucleoli, stimulate host cells to produce ROS, and promote host cell apoptosis. However, the mechanism of the host-pathogen interaction leading to host oxidative stress and cell cytotoxic effects such as DNA damage remains to be elucidated. Here, we used Cell Counting Kit-8 (CCK-8) assays and 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-OHdG) ELISA to study cell viability and DNA oxidative damage level after exposure to EspF. Western blot and immunofluorescence were also used to determine the level of the DNA damage target protein p-H2AX and cell morphology changes after EspF infection. Moreover, we verified the toxicity in intestinal epithelial cells mediated by EspF infection in vivo. In addition, we screened the host proteins that interact with EspF using CoIP-MS. We found that EspF may more depend on its C-terminus to interact with SMC1, and EspF could activate SMC1 phosphorylation and migrate it to the cytoplasm. In summary, this study revealed that EspF might mediate host cell DNA damage and found a new interaction between EspF and the DNA damage repair protein SMC1. Thus, EspF may mediate DNA damage by regulating the subcellular localization and phosphorylation of SMC1.